Initial Research on Mercury in some Coal - Fired Thermal Power Plants of Vietnam - Khải, Nguyễn Mạnh (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1S, 2017)
Coal-fired thermal power plants play an important role in Vietnam's power structure, which currently mainly use domestic coal. In addition to securing national energy security, coal-fired power plants also have potential environmental problems if not being properly managed and controlled in relation to dust and air emissions, wastewater, solid waste (clinker and fly ash). Curently, 19 coal-fired thermal power plants have been operating stably with two common types of boiler technology pulverizing coal (PC) and circulating fluidized bed (CFB), of which PC takes majority (12/19 installed power plants with capacity is 9779MW/12.509MW). The coal-fired power plant of Vietnam is currently designed to use anthracite domestic coal. This type of coal although has a lower mercury content than peat, brown coal (the major raw material for thermal power sector in the US and European countries), but not be excluded when referring to fossil fuels. The mercury contents in raw coal used in 04 thermal power plants (which are Uong Bi 2 extension, Quang Ninh, Cao Ngan, Mong Duong 1) were ranged from 0.12-0.82mg/kg. After combustion, the mercury is mainly distributed in the vapor phase of the exhaust gas (comparable with dust, ash, slag). Therefore, the control of mercury in the thermal power plants needs to focus on emissions instead of concerns about ash and slag.